A companion to American sport history - Riess, Steven A. (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2014)
"A Companion to American Sport History presents a collection of original essays that represent the first comprehensive analysis of scholarship relating to the growing field of American sport history. Presents the first complete analysis of the scholarship relating to the academic history of American sport ; Features contributions from many of the finest scholars working in the field of American sport history ; Includes coverage of the chronology of sports from colonial times to the present day, including major sports such as baseball, football, basketball, boxing, golf, motor racing, tennis, and track and field ; Addresses the relationship of sports to urbanization, technology, gender, race, social class, and genres such as sports biography"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Sports -- United States -- History; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; Sports; United States; Electronic books; History; Electronic books